The investigation and analysis of the current situation of medical service price cognition of China with grey relational analysis theory. Issue 2 (1st April 2019) - Yin, Lili; Duan, Lizhong; Zhang, Yinran; Liu, Hangyu; Zhang, Chongxu; Sun, Qiaoqiao; Lu, Qi
Abstract : Purpose: Through a questionnaire survey, the purpose of this paper is to understand and analyse the cognitions of medical service price of medical workers in various regions of China, and discuss the policy suggestions on the price dynamic adjustment of medical service. Design/methodology/approach: The authors conducted a questionnaire survey on the cognition of medical service price medical workers in various regions of China, and then the grey relational analysis theory is used to analyse the data obtained from the questionnaire survey. Findings: The investigation and analysis shows some cognitions of hospital workers on the price of medical services in various regions in China, the authors analyse the results of grey relational analysis and come up with suggestions for relevant departments. Research limitations/implications: Although a plenty of research on the current situation of medical service price cognition of China is discussed in the paper, it is not complete; thus, a large amount of information needs to be consulted further. The data obtained from the questionnaire are less used and the utilisation rate is lower, which may result in one-sided results and need further investigation. Practical implications: Through the investigation and analysis, the authors can determine about the implementation of medical service prices in various parts of China from the perspective of hospital workers to a certain degree, and try to explore the relevant policy recommendations for the dynamic adjustment of medical service prices. Social implications: The price of medical services refers to the fees for registration, diagnosis, inspection, surgery, nursing and medicine. In a narrow sense, the price of medical services refers to the standard of charge for medical services except drugs. This paper mainly refers to the narrow sense. As one of the important means and methods for the government to control the medical service market, medical service price is also an important basis for the economic source of medical institutions. The adjustment of medical service price is related to the interests of all aspects of society. Originality/value: Medical service price is an important basis for the economic source of medical institutions, the adjustment of medical service price is related to the interests of all aspects of society and it is a hot issue of social concern. Through the investigation and analysis, the authors use grey relational analysis to know about the medical service prices in various parts of China from the perspective of hospital workers to a certain degree, and try to explore the relevant policy recommendations for the dynamic adjustment of medical service prices.